EFFECT OF TAX REFORM ON IT FIRM IN NIGERIA - Otiya, Simon Zira; Usman, Dahiru Haruna (FUDMA JOURNAL OF SCIENCES, 2026)
To improve the efficacy and efficiency of taxes, tax reforms in Nigeria's information technology (IT) sector are now required. Many people have acknowledged the dynamic implications of these reforms on the growth and functioning of the Nigerian tax system. According to this study, tax reform has a significant positive impact on both the nation's economic growth and the operations of IT companies. The study presents evidence using robust least squares regression on Tax Optimization Metrics (effective tax rate, or ETR, and marginal tax rate, or MTR) against Return on Assets (ROA) by examining secondary data from five ICT companies listed on the Nigerian Stock Exchange (providing services between 2014 and 2023). Evidence regarding the effects of the VAT, Petroleum Profit Tax (PPT), Companies Income Tax (CIT), and Customs and Excise Duties (CED) reforms on revenue generated and GDP in Nigeria was also presented, backed by time-series analyses spanning 2013–2022.According to the findings, ROA for Nigerian IT companies is positively impacted by increases in ETR. On the other hand, ROA has been found to be significantly and negatively impacted by MTR declines. Further analysis shows that whereas VAT had a detrimental impact on Nigeria, PPT and CIT considerably boosted the country's economic growth. Additionally, the change of customs and excise duties had no statistically significant impact on economic growth.The study's conclusions show that tax reforms benefit operations by lowering compliance costs for small and medium-sized enterprises (SMEs) in Nigeria's rapidly expanding IT sector. At the same time, they raise operating expenses
Keywords: Effect; Tax; Performance; Information Technology; Firms